Extreme Learning Machine and Particle Swarm Optimization in optimizing CNC turning operation - Janahiraman T.V.; Ahmad N.; Nordin F.H. (Institute of Physics Publishing, 2023)
Computer control systems; Knowledge acquisition; Learning systems; Manufacture; Particle swarm optimization (PSO); Turning; Artificial intelligent techniques; Extreme learning machine; In-process parameters; Modelling techniques; Optimal cutting parameters; Optimization techniques; Performance functions; Traditional techniques; Swarm intelligence